2013
DOI: 10.1016/j.prevetmed.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic disease risk perceptions and infection control practices of Australian veterinarians: Call for change in work culture

Abstract: This is an author-produced PDF of an article published in Preventive Veterinary Medicine, AbstractThis study was conducted to determine the perceptions of zoonotic disease risk among Australian veterinarians, the infection control practices they use to protect themselves from zoonotic diseases, and the factors influencing their use of these protective practices. A questionnaire was designed and piloted prior to its administration to veterinarians at the annual Australian Veterinary Association Conference in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 22 publications
2
63
2
8
Order By: Relevance
“…Teaching veterinarians to treat every sick horse with a fever or respiratory symptoms as a potential threat to human health has also involved a major cultural shift: from overalls to Hazmat suits, and from an easy familiarity with the bodies of sick animals to hyper-vigilance (Dowd et al, 2013). Perhaps because two of the four people who have died of HeV were veterinarians who went off to work one day and caught the disease, some veterinarians have quit equine practice (Mendez et al, 2012), and many now refuse to treat unvaccinated horses (Mendez et al, 2013).…”
Section: Of Hendra Horses and Public Ordermentioning
confidence: 99%
“…Teaching veterinarians to treat every sick horse with a fever or respiratory symptoms as a potential threat to human health has also involved a major cultural shift: from overalls to Hazmat suits, and from an easy familiarity with the bodies of sick animals to hyper-vigilance (Dowd et al, 2013). Perhaps because two of the four people who have died of HeV were veterinarians who went off to work one day and caught the disease, some veterinarians have quit equine practice (Mendez et al, 2012), and many now refuse to treat unvaccinated horses (Mendez et al, 2013).…”
Section: Of Hendra Horses and Public Ordermentioning
confidence: 99%
“…The findings of this study are supported by a previous study with Australian veterinarians, which also suggested the need for more practical biosecurity training as it found little uptake of appropriate personal protective equipment use in practice. 11 Younger veterinarians may have lower levels of biosecurity compliance similar to younger horse owners 19 . Implementing biosecurity measures might be perceived as a greater inconvenience by younger veterinarians due to the associated costs in terms of time and effort, making it less practical for them to perform than for older veterinarians.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, and the potential for contracting zoonotic infections, about half of the veterinarians questioned at a national veterinary conference perceived that they were at low level of risk of being exposed to zoonotic diseases from various animal species and procedures [61]. The reasons for this perception are not clear but maybe reflect a certain complacency that the species 'barrier' may protect them whilst working with pets.…”
Section: Paradigm 4: Cvbd Veterinarians and Public Healthmentioning
confidence: 99%
“…The reasons for this perception are not clear but maybe reflect a certain complacency that the species 'barrier' may protect them whilst working with pets. Indeed, the same study found that small animal practitioners were three times less likely than their large animal colleagues to use adequate personal protective equipment (PPE) [61]. In the USA, Bartonella seroreactivity and bacteraemia were documented in approximately one half (49.5%) and a quarter (23.9%) of the individuals, respectively, of persons (n=192) who reported animal exposure, most of whom also reported animal scratches and/or bites [60].…”
Section: Paradigm 4: Cvbd Veterinarians and Public Healthmentioning
confidence: 99%
See 1 more Smart Citation